INFLUENCE OF ULŪ AL-ALBĀB ON INNOVATION THROUGH KNOWLEDGE TRANSFER AMONG ICT FIRMS - Mhd Sarif , Suhaimi; Ismail , Yusof (Online Journal of Islamic Management and Finance (OJIMF), 2024)
This study investigates the viewpoints of managers in information and communication technology (ICT) firms regarding Ulū al-Albāb influence in promoting innovation through knowledge transfer. This study argues that stickiness in knowledge transfer hindered promotion. However, Ulū al-Albāb reduces stickiness in knowledge transfer among ICT firms for innovation. The study reveals that Ulū al-Albāb with policy instrument aimed at facilitating knowledge transfer for innovation in the advancement of science and technology, encourages knowledge transfer among ICT firms. The study found that the influence of Ulū al-Albāb enable knowledge workers in the ICT firms to effectively employ their wisdom, religiosity, and spirituality to promote the knowledge transfer. Thus, the study suggests that the incorporation of Ulū al-Albāb in the policy instrument with the policies of science and technology parks to promote innovation among ICT firms.